Alkalinity of cement mortar containing different types of supplementary cementitious materials under accelerated curing conditions / Sumra Yousuf - Sumra , Yousuf (2021)
Cement-based materials (CBMs) such as paste, mortar and concrete are the most dominant construction materials of structures. They are highly alkaline, with a pH in the range of 12.0 to 13.5, due to Ca(OH)2 contents (portlandite). The strength-gaining rate and hardening process of CBMs under normal curing conditions are slow. Therefore, accelerated curing methods are applied for gaining high early-age strength, especially in prefabrication industry. The CBMs subjected to an initial high curing temperature undergo accelerated hydration resulting in non-uniform scattering of hydration products. It creates a high porosity and reduction in compressive strength at later ages, called the phenomenon of crossover effect (COE). On the other hand, there is this belief that using supplementary cementitious materials (SCMs) in CBMs reduces Ca(OH)2 contents in the process of formation of secondary gel, resulting reduction of pH value. As the pH value and COE affecting both mechanical and durability properties of CBMs, therefore, the pH and COE of pure and blended CBMs under different curing conditions and for short and long terms should be studied. The main objective of this research is to study the short and long-term pH values of cement mortar incorporating various types of SCMs in low and high volumes under normal and accelerated curing methods. For monitoring the COE phenomenon, the compressive strength of mortar samples was measured in short and long terms. For measuring the pH value, the inner portion of samples was taken and grinded using grinding machine. The prepared powder was mixed with water in dilution ratio of 1:2 to make the solution and then the pH readings were taken by digital pH meter. The thermal gravimetric analysis (TGA) test was used to determine Ca(OH)2 contents for the mortars. In addition, measurements were conducted for the specimens after exposure to high temperatures of 200, 400, 600 and 800 ℃. The results showed that COE was observed in OPC control and blended cement mortars incorporating FA, GGBFS, ground and treated palm oil fuel ash (G-POFA and T-POFA)) from 56-150 days. However, it was less than 10% for all types of these mortars. The pH of blended cement mortars was less than the control OPC mortar at the same age and curing conditions. A decreasing trend was found for the pH of almost all the cement mortars with curing age up to 150 days. It was observed that different curing conditions has no significant effect on the pH of cement mortars at the same curing age. Results confirmed that the pH of CBMs does not remain constant with ageing. There was a decreasing trend in pH and Ca(OH)2 contents by increasing replacement volumes of SCMs with OPC in the blended cement mortars. In addition, from the TGA test result, it was confirmed that the pH of CBMs is not only dependent on the Ca(OH)2 content and other factors must be investigated.